USING OF THE "VIRTUAL WALL PADLET" ON PRACTICAL LESSON IN HIGHER EDUCATIONAL ESTABLISHMENT - Kachaniuk, Natalia V. (Educological discourse, 2014)
The article presents a brief analysis of Web-resources for organization of student’s group-work; the benefits of virtual walls Padlet were examined; example of designed and implemented practical lesson using virtual wall Padlet at the university was suggested: the results of the student’s poll concerning effectiveness of using virtual wall Padlet during practical lesson are covered.